2015
DOI: 10.1021/acssynbio.5b00037
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Electrostatics on Small Molecule Flux through a Protein Nanoreactor

Abstract: Nature uses protein compartmentalization to great effect for control over enzymatic pathways, and the strategy has great promise for synthetic biology. In particular, encapsulation in nanometer-sized containers to create nanoreactors has the potential to elicit interesting, unexplored effects resulting from deviations from well-understood bulk processes. Self-assembled protein shells for encapsulation are especially desirable for their uniform structures and ease of perturbation through genetic mutation. Here,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
66
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(71 citation statements)
references
References 51 publications
3
66
1
Order By: Relevance
“…Similarly, if the permeability of the MCP to propionaldehyde is sufficiently low, the permeability to 1,2-PD can be increased to saturate PduP/Q. This putative trapping mechanism is in congruence with the in vitro observation that small molecule efflux from a protein nanoreactor can be affected by the chemical character of the reactor pores [35]. Studies of substrate channeling in enzyme scaffolds also emphasize the importance of creating a high substrate concentration in the vicinity of downstream enzymes [28, 36].…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Similarly, if the permeability of the MCP to propionaldehyde is sufficiently low, the permeability to 1,2-PD can be increased to saturate PduP/Q. This putative trapping mechanism is in congruence with the in vitro observation that small molecule efflux from a protein nanoreactor can be affected by the chemical character of the reactor pores [35]. Studies of substrate channeling in enzyme scaffolds also emphasize the importance of creating a high substrate concentration in the vicinity of downstream enzymes [28, 36].…”
Section: Discussionsupporting
confidence: 53%
“…The permeability we predict is much lower than would be estimated based on free diffusion through an area equivalent to the cumulative area of the pores in the MCP shell (on the order of 1 − 10 cm/s). The phenomenon of surprisingly low apparent permeability of a protein shell has been predicted previously [35], and is likely rooted in the fact that the Debye length, governing the distance at which electronic interactions occur between the amino acid residues lining the pore and the client small molecules, extends across the entire pore area. Excluded-volume models of apparent diffusivity in the pore, therefore, do not apply.…”
Section: Discussionmentioning
confidence: 91%
“…However, recent structures of carboxysome shell proteins offer a potential mechanism for differential permeability of CO 2 and HCO 3 − : The pores of shell proteins typically carry positive charge, which might increase the rate of HCO 3 − transit relative to CO 2 (12,49). Indeed, recent experimental evidence suggests that protein compartments can be selectively permeable (50,51). Intuitively, it seems that a very high HCO 3 − permeability and a very low CO 2 permeability would be best for the efficient operation of the CCM.…”
Section: S Elongatus Cyotosolic Ph Is Within the Optimal Range For Ccmmentioning
confidence: 99%
“…Tagging the enzymes with SpyCatcher and bacteriophage MS2 capsid protein with SpyTag resulted in assembly of particles in E. coli that increased indigo production by 60% compared to controls (Giessen and Silver, 2016). Pores of BMCs and capsids can be engineered to control substrate uptake specificity (Glasgow et al, 2015). Isolated capsids showed that the enzymes were markedly more stable in vitro because of the covalent linkages.…”
Section: Nanoreactorsmentioning
confidence: 99%